Glucose inhibits glucagon secretion by decreasing [Ca2+]c and by reducing the efficacy of Ca2+ on exocytosis via somatostatin-dependent and independent mechanisms - Bilal Singh; Firas Khattab; Patrick Gilon (Elsevier, 2022)
Objective: The mechanisms by which glucose stimulates insulin secretion from β-cells are well established and involve inhibition of ATP-sensitive K+ (KATP) channels, followed by a rise in [Ca2+]c that triggers exocytosis. However, the mechanisms by which glucose controls glucagon release from α-cells are much less known. In particular, it is debated whether the sugar controls glucagon secretion by changing α-cell [Ca2+]c, and whether KATP channels or paracrine factors are involved. The present study addresses these issues. Methods: We tested the effect of a decrease or an increase of glucose concentration (Gx, with x = concentration in mM) on α-cell [Ca2+]c and glucagon secretion. α-cell [Ca2+]c was monitored using GluCreGCaMP6f mice expressing the Ca2+-sensitive fluorescent protein, GCaMP6f, specifically in α-cells. [Ca2+]c was compared between dispersed α-cells and α-cells within islets to evaluate the potential contribution of an indirect effect of glucose. The same protocols were used for experiments of glucagon secretion from whole islets and [Ca2+]c measurements to test if changes in glucagon release mirror those in α-cell [Ca2+]c. Results: Blockade of KATP channels by sulfonylureas (tolbutamide 100 μM or gliclazide 25 μM) strongly increased [Ca2+]c in both dispersed α-cells and α-cells within islets. By contrast, glucose had no effect on [Ca2+]c in dispersed α-cells, whereas it affected it in α-cells within islets. The effect of glucose was however different in islets expressing (Sst+/+) or not somatostatin (SST) (Sst−/−). Decreasing glucose concentration from G7 to G1 modestly increased α-cell [Ca2+]c, but to a slightly larger extent in Sst+/+ islets than in Sst−/− islets. This G1-induced [Ca2+]c rise was also observed in the continuous presence of sulfonylureas in both Sst+/+ and Sst−/− islets. Increasing glucose concentration from G7 to G20 did not affect α-cell [Ca2+]c in Sst+/+ islets which remained low, whereas it strongly increased it in Sst−/− islets. The observations that this increase was seen only in α-cells within islets but never in dispersed α-cells and that it was abrogated by the gap junction inhibitor, carbenoxolone, point to an indirect effect of G20 and suggest that, in Sst−/− islets, G20-stimulated β-cells entrain α-cells whereas, in Sst+/+ islets, the concomitant release of SST keeps α-cell [Ca2+]c at low levels. The [Ca2+]c lowering effect of endogenous SST is also supported by the observation that SST receptor antagonists (SSTR2/3) increased [Ca2+]c in α-cells from Sst+/+ islets. All these [Ca2+]c changes induced parallel changes in glucagon release. To test if glucose also controls glucagon release independently of [Ca2+]c changes, additional experiments were performed in the continuous presence of 30 mM K+ and the KATP channel opener diazoxide (250 μM). In these conditions, α-cell [Ca2+]c within islets was elevated and its steady-state level was unaffected by glucose. However, decreasing the glucose concentration from G7 to G1 stimulated glucagon release whereas increasing it from G1 to G15 inhibited it. These effects were also evident in Sst−/− islets, and opposite to those on insulin secretion. Conclusions: We propose a model according to which glucose controls α-cell [Ca2+]c and glucagon secretion through multiple mechanisms. Increasing the glucose concentration modestly decreases [Ca2+]c in α-cells independently of their KATP channels and partly via SST. The involvement of SST increases with the glucose concentration, and one major effect of SST is to keep α-cell [Ca2+]c at low levels by counteracting the effect of an entrainment of α-cells by β-cells when β-cells become stimulated by glucose. All these [Ca2+]c changes induce parallel changes in glucagon release. Glucose also decreases the efficacy of Ca2+ on exocytosis by an attenuating pathway that is opposite to the well-established amplifying pathway controlling insulin release in β-cells.